On the observed diversity of star formation efficiencies in Giant Molecular Clouds. Issue 4 (2nd May 2019) - Grisdale, Kearn; Agertz, Oscar; Renaud, Florent; Romeo, Alessandro B; Devriendt, Julien; Slyz, Adrianne
Abstract: Observations find a median star formation efficiency per free-fall time in Milky Way Giant Molecular Clouds (GMCs) of the order of$ε _{\rm ff}\sim 1{{\ \rm per\ cent}}$ with dispersions of${\sim }0.5\, {\rm dex}$ . The origin of this scatter in ϵff is still debated and difficult to reproduce with analytical models. We track the formation, evolution and destruction of GMCs in a hydrodynamical simulation of a Milky Way-like galaxy and by deriving cloud properties in an observationally motivated way, we measure the distribution of star formation efficiencies which are in excellent agreement with observations. We find no significant link between ϵff and any measured global property of GMCs (e.g. gas mass, velocity dispersion). Instead, a wide range of efficiencies exist in the entire parameter space. From the cloud evolutionary tracks, we find that each cloud follows a unique evolutionary path which gives rise to a wide diversity in all properties. We argue that it is this diversity in cloud properties, above everything else, that results in the dispersion of ϵff .